Evaluasi Pasca Huni Aspek Fungsional pada Rumah Sakit Hewan Dinas Peternakan Provinsi Jawa Timur - Fitriani, Desi; Sholahuddin, Muhamad; Prasetyaningsih, Yulyta Kodrat (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2025)
Animal hospitals are medical facilities that provide health care for animals. As public awareness of the importance of animal health increases, expectations for animal hospital services also rise. Therefore, the facilities available should reflect the professionalism and commitment of animal hospitals to the welfare of animals and humans. This study aims to evaluate the functional aspects of the interior of the East Java Provincial Livestock Service Animal Hospital through an indicative post-occupancy evaluation method using a qualitative and quantitative approach. The main focus of the study is to analyze the functional performance of the interior in supporting veterinary medical services. Data collection methods included interviews, questionnaires, field observations, and literature reviews. Based on the observations, several functional issues were identified. Therefore, this study is important to identify existing problems, analyze their causes, and formulate appropriate solutions to optimize building functionality according to user needs. The research results indicate that most of the spaces within the animal hospital meet functional standards, although some criteria remain suboptimal, namely human factors, furniture and storage, as well as flexibility and change. This study is expected to provide recommendations for improving the quality of existing animal hospital facilities and serve as a reference for developing optimal animal hospital designs in the future.